THE DIALECTICS OF THE COGNITIVE AND NON-COGNITIVE IN THINKING STYLE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines the interplay between cognitive and non-cognitive elements in human thinking styles through a dialectical perspective. The synthesis of these dimensions plays a crucial role in reasoning, creativity, and decision-making processes.